2017
DOI: 10.3389/fimmu.2017.00088
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus durans EP1 a Promising Anti-inflammatory Probiotic Able to Stimulate sIgA and to Increase Faecalibacterium prausnitzii Abundance

Abstract: Enterococcus species, principally Enterococcus faecium are used as probiotics since a long time with preference in animal applications but safety considerations were updated and also new uses as probiotics can be envisaged. Fifteen Enterococcus strains isolated from different foods were identified and analyzed for virulence factors and antibiotic resistance. Three Enterococcus durans strains were selected to study their immunomodulatory properties on PBMC and Caco2 cells. Two strains presented a profile toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 79 publications
1
31
0
1
Order By: Relevance
“…As with other studies (36,38), our adhesion assays were performed using porcine mucin. Even though galactose, N-acetylglucosamine, fucose, and sialic acid are the most common carbohydrates in both porcine and mouse mucin (39,40), the structures of the mucin glycans differ between mouse mucin and porcine mucin.…”
Section: Discussionmentioning
confidence: 99%
“…As with other studies (36,38), our adhesion assays were performed using porcine mucin. Even though galactose, N-acetylglucosamine, fucose, and sialic acid are the most common carbohydrates in both porcine and mouse mucin (39,40), the structures of the mucin glycans differ between mouse mucin and porcine mucin.…”
Section: Discussionmentioning
confidence: 99%
“…A higher abundance of F. prausnitzii was detected in the microbiota of H. pylori -negative parents. F. prausnitzii has been reported to be one of the bacterial species possessing anti-inflammatory properties ( 25 , 26 ), and higher abundances of this species were detected preferentially in Japanese subjects with lean body mass ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…durans TN-3 suppressed the development of dextran sodium sulfate DSS colitis via the induction of IL-10 producing Treg cells (Kanda et al, 2016 ). Another recent study have reported that E. durans EP1 modulates gut microbiota by increasing Faecalibacterium prausnitzii , a functionally important bacterium in some cases of dysbiosis (Carasi et al, 2017 ).…”
Section: Therapeutic Potential Of Enterococcal Bacteriocinsmentioning
confidence: 99%
“…This novel anti-inflammatory bacterium may be preferentially useful as a prophylactic treatment to avoid inflammatory bowel disease (Avram-Hananel et al, 2010 ). More recently, administration of E. durans EP1 was found to increase the amount of Faecalibacterium prausnitzii , a butyrate-producing bacteria, which is known for its anti-inflammatory effects (Carasi et al, 2017 ).…”
Section: Therapeutic Potential Of Enterococcal Bacteriocinsmentioning
confidence: 99%